Parent Participation in Improving the Quality of Educational Institutions - Muslimin, Ikhwanul; Yasin, Muhamad (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2023)
This study examines parental participation in educational institutions. Parents are the key to the success of a learning process at school because of their very important role, and the quality of educational institutions becomes superior if parents take part in the implementation of education. The approach used in this research is qualitative with a literature study method, researchers use several books, journals, and the results of recent observations as references. The findings reveal that parents' participation in improving the quality of educational institutions is because 1) the position of parents is very vital in educational institutions, including the results of their contributions in the form of thoughts, skills (certain expertise that a person has and can be applied in an activity), energy, property, and money. Then, the position of parents also plays a role in providing a conducive learning environment so that students can learn calmly and pleasantly; 2) synergy between schools and families (parents), and actively involved in assisting learning efforts and student development.